Persaingan Antar Bos Karet (Pengepul Karet) di Desa Lumbang Kecamatan Muara Uya Kabupaten Tabalong Tahun 2000-2015 - Raji, Fahrul; Anis, Mohamad Zaenal Arifin; Prawitasari, Melisa (Lambung Mangkurat University, 2021)
A Rubber is the most potential plantation crop in Tabalong Regency. Tabalong Regency especially in Lumbang Village. Many villagers work as rubber farmers. The farmers sell their tapped products to the rubber boss. This rubber boss plays an important role in the economy of rubber farmers. The number of rubber bosses in Lumbang Village from 2000-2015 were 16 people. The number of rubber bosses indirectly creates competition between rubber bosses. The purpose of this study was to determine the background of being a rubber boss, competition among rubber bosses, and the impact of the competition between rubber bosses in Lumbang Village. This research uses historical method with heuristic, criticism, interpretation, and historiography stages. The results of this study indicate that the background of the Lumbang residents to choose to work as rubber bosses due to economic factors, the busy trading business of rubber, and hereditary employment. Competition between rubber bosses is divided into 3 forms, namely: the courage to determine the price of rubber higher than other rubber bosses, rubber bosses buy good quality rubber first than other rubber bosses, and compete to win over rubber farmers. The competition between rubber bosses in Lumbang Village has positive and negative impacts on both the farmers and rubber bosses.